1999
DOI: 10.1088/0953-8984/11/41/322
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the comment on `Inhomogeneities and birefringence in quartz'

Abstract: The ferroelasticity effect of the incommensurate phase of quartz is discussed. It is pointed out that the effect discussed in the paper by Saint-Grégoire et al (Saint-Grégoire P, Snoeck E, Roucau C, Luk'yanchuk I and Janovec V 1996 JETP Lett. 64 410) is negligibly small, and cannot explain the anomalous observations near the transition in quartz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The situation in which the IC third-harmonic modulation amplitude is larger than the amplitude of the fundamental modulation b/3 + κ has been also discussed by the present authors [22]. It was shown [22] that such a situation directly follows from the Landau theory near the lock-in transition, when κ → 0, and that the amplitude of the third-harmonic modulation increases as κ −1 . More detailed analysis of the above-described situation will be published elsewhere.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The situation in which the IC third-harmonic modulation amplitude is larger than the amplitude of the fundamental modulation b/3 + κ has been also discussed by the present authors [22]. It was shown [22] that such a situation directly follows from the Landau theory near the lock-in transition, when κ → 0, and that the amplitude of the third-harmonic modulation increases as κ −1 . More detailed analysis of the above-described situation will be published elsewhere.…”
Section: Introductionsupporting
confidence: 60%
“…In our paper [19], we also discussed earlier calculations of the Debye-Waller factors for the IC structures carried out by Overhauser [20] and by Axe [21]. The situation in which the IC third-harmonic modulation amplitude is larger than the amplitude of the fundamental modulation b/3 + κ has been also discussed by the present authors [22]. It was shown [22] that such a situation directly follows from the Landau theory near the lock-in transition, when κ → 0, and that the amplitude of the third-harmonic modulation increases as κ −1 .…”
Section: Introductionsupporting
confidence: 56%
“…In their theoretical works, Aslanyan et al [11,13] gave no indication of the temperature range of the two ferroelastic phases. However, in recent measurements of LS and optical depolarization, Shigenari et al [41,59] have observed a fog zone and an m-zone (corresponding to our LAS and SAS regions) in two successive temperature ranges of 0.3 and 0.2 K, as shown in figure 4(b).…”
Section: Thermal Conditionsmentioning
confidence: 98%
“…Recently, Saint-Grégoire et al [10] and Aslanyan et al [11] introduced two new models, where the quartz opalescence is explained by the existence of new inc ferroelastic phases, stable in a finite temperature range above T c . However, they proposed very different microscopic structures for these new phases, which has led to further controversy between the two groups [12,13]. We now briefly introduce these two ferroelastic models; our criticisms are developed, in section 4, in relation to experimental results…”
Section: Inc Ferroelastic Phase Models Of the Quartz Opalescencementioning
confidence: 99%
See 1 more Smart Citation